Food waste handling in Malaysia and comparison with other Asian countries - Lim, W. J.; Chin, Nyuk Ling; Yusof, A. Y.; Yahya, A.; Tee, Tuan Poy (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
The increasing amount of food waste in Malaysia in recent years has brought many environmental issues in the country where it affects the nation’s solid waste management framework. At the moment, the government is limited to other alternatives of food waste disposal besides the conventional landfill and incineration methods. This paper provides information on the current status of food waste handling, management, regulations, and policies in Malaysia. It helps to draw the problem and challenge to a clearer view in efforts of achieving sustainable and integrative food waste handling in the country.